In vitro and in vivo assessment of a new acellular human amnion/chorion membrane device for guided bone regeneration - Paul Galvez; Naïma Ahmed Omar; Robin Siadous; Marlène Durand; Léo Comperat; Xavier Lafarge; Florelle Gindraux; Loïc Sentilhes; Jean-Christophe Fricain; Nicolas L’Heureux; Mathilde Fenelon (Scientific Reports)
Abstract Thanks to its unique biological properties, the human amniotic membrane (AM) has shown promising results for guided bone regeneration (GBR), but displays some limitations such as poor space-maintaining ability. This study thus aimed to develop a new amnion/chorion membrane (ACM), with better mechanical properties as well as comparable or improved biological properties for GBR. We first developed a new decellularization method of ACM (DL-ACM) which was validated by DNA staining and quantification, and its cytocompatibility was established in vitro. The thickness of DL-ACM was significantly increased over thirty-fivefold, and its tearing strength and compression strength significantly increased more than tenfold compared to the decellularized AM (DL-AM). In vivo, DL-ACM demonstrated its biocompatibility subcutaneously, and its osteogenic properties were compared to DL-AM and a gold standard membrane in a GBR defect model in rats. Micro-CT and histomorphometric analysis showed that DL-ACM significantly promoted early bone regeneration after 1 week and significantly increased bone regeneration compared to the empty defect and the gold standard membrane over time. In this study, we developed a simple and reproducible method to produce an acellular, non-cytotoxic, and biocompatible DL-ACM. This new membrane is as effective as AM to promote early bone regeneration while demonstrating better biomechanical properties.